Analysis of the Current Research Status of Life Cycle Assessment Method Applications in the Leather Industry - Minmin LIU; Qianchuan ZHOU; Chunhua WANG; Yuanhang XIAO; Wei LIN (Pige Kexue Yu Gongcheng, 2024)
Leather industry, a traditional pillar of China's light industry with international competitive advantages, is developing towards green and low-carbon transformation and upgrading. Life Cycle Assessment (LCA), as a systematic and comprehensive evaluation method, can be used to quantify the resource and environmental impacts of leather manufacturing process. This paper briefly reviewed the development history, standard procedures, and theoretical frameworks of the LCA methodology. It focuses on the current research status of LCA applications in the leather industry and its guiding role in pollution reduction and carbon mitigation, as well as existing problems and solutions. The carbon footprint database for leather products was established based on the authors’ research and practice in developing standard methods for calculating the carbon footprint of leather products and constructing a database of carbon emission factor for leather chemicals. The authors further proposed the construction of a LCA environmental impact prediction model for tanning processes, with the aim of enabling green, low-carbon leather manufacturing and high-quality development of the leather industry.